Tissue Factor Pathway Inhibitor, Activated Protein C Resistance, and Risk of Coronary Heart Disease Due To Combined Estrogen Plus Progestin Therapy. Issue 2 (February 2016) - Johnson, Karen C.; Aragaki, Aaron K.; Jackson, Rebecca; Reiner, Alex; Sandset, Per Morten; Rosing, Jan; Dahm, Anders E.A.; Rosendaal, Frits; Manson, JoAnn E.; Martin, Lisa W.; Liu, Simin; Kuller, Lewis H.; et al.
Abstract : Objective—: To examine whether tissue factor pathway inhibitor or acquired activated protein C (APC) resistance influences the increased risk of coronary heart disease (CHD) due to estrogen plus progestin therapy. Approach and Results—: Prospective nested case–control study of 205 cases of CHD and 481 matched controls in the Women's Health Initiative randomized trial of estrogen plus progestin therapy. After multivariable covariate adjustment, both baseline tissue factor pathway activity ( P =0.01) and APC resistance ( P =0.004) were associated positively with CHD risk. Baseline tissue factor pathway activity and APC resistance singly or jointly did not significantly modify the effect of estrogen plus progestin on CHD risk. Compared with placebo, estrogen plus progestin decreased tissue factor pathway inhibitor activity and increased APC resistance but these changes did not seem to modify or mediate the effect of estrogen plus progestin on CHD risk. Conclusions—: Tissue factor pathway inhibitor activity and APC resistance are related to CHD risk in women, but may not explain the increased CHD risk due to estrogen plus progestin therapy. The data from this study do not support the clinical use of measuring these hemostatic factors to help stratify risk before hormone therapy. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT00000611. Abstract : Supplemental Digital Content is available in the text.